1999
DOI: 10.1001/archinte.159.19.2306
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective, Randomized Trial to Assess the Cost Impact of Pharmacist-Initiated Interventions

Abstract: Background: Hospital pharmacists make many recommendations that improve patients' quality of care and/or reduce drug costs. While the impact of quality-of-care interventions is difficult to quantify, those limited to cost savings could be assessed in a prospective, randomized fashion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
94
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(96 citation statements)
references
References 16 publications
1
94
0
1
Order By: Relevance
“…It is interesting that for these two statements the mean scores of agreement were among the lowest for all three professional groups. Despite many reports about a positive economic impact of clinical pharmacists' activities in the literature (18)(19)(20)(21)(22)(23)(24)(25)(26)(27), physicians and nurses found those clinical pharmacists' activities less important. Budgeting and cost containment in the hospital is the responsibility of managers rather than pharmacists.…”
Section: The Role Of a Clinical Pharmacist In The Hospital Systemmentioning
confidence: 97%
“…It is interesting that for these two statements the mean scores of agreement were among the lowest for all three professional groups. Despite many reports about a positive economic impact of clinical pharmacists' activities in the literature (18)(19)(20)(21)(22)(23)(24)(25)(26)(27), physicians and nurses found those clinical pharmacists' activities less important. Budgeting and cost containment in the hospital is the responsibility of managers rather than pharmacists.…”
Section: The Role Of a Clinical Pharmacist In The Hospital Systemmentioning
confidence: 97%
“…The clinical pharmacy process involves identifying potential and actual DRPs, resolving actual DRPs and preventing potential DRPs. Previous studies have demonstrated that clinical pharmacy services for in-patients reduce the number of drug-related problems [12], the length of stay [13][14][15][16], costs [13,[16][17], adverse drug reactions [18], rates of readmission [14][15] and rates of drug-related readmission [19].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical interventions made by pharmacists improve patient care and result in cost savings for institutions. [1][2][3][4][5][6][7][8][9][10][11][12] Intervention data can be useful in providing information to other health care providers or health care system administrators regarding the value of clinical pharmacy services. This documentation also may be used to justify salaries for current pharmacist positions or to validate the need for additional pharmacist positions.…”
Section: Introductionmentioning
confidence: 99%
“…While there are numerous published studies regarding documentation of pharmacists' clinical services, [1][2][3][4][5][6][7][8][9][10][11][12] the studies on the impact of clinical services performed by pharmacy students, residents, and faculty members are less robust. Student pharmacists must learn and appropriately apply documentation skills so that doing so will become a professional habit that is continued after graduation.…”
Section: Introductionmentioning
confidence: 99%